ANALISIS FISKAL DAERAH, BELANJA DAERAH DAN KINERJA EKONOMI: STUDI KASUS KABUPATEN/KOTA DI JAWA TENGAH - Sutris no; Susi lo (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study analyzes the role of local government in economic performance in Central Java Province. The role of government in the economy can be seen from the analysis of the local fiscal impact on econommic performing, and local government spending on economic performance in the districts/towns in Central Java province. By using Partial Least Square analysis (PLS) was concluded that the source of local fiscal has positive influence on local government spending significant, local government spending has significant effect on economic performance as measured by statistics. Keywords: Region Fiscal Source, Expenditures, Economic Performance, Partial Least Square.